Situation Analysis of Implementation of National Health Programmes in Primary Health Centres (Phcs) At Uttarakhand - Jha, Nishu; Jain, Bhavna; Bhati, Radhika; Mehta, Aprajita; Dhinwa, Manisha; Kishore, Surekha; Aggarwal, Pradeep; Job, Sheen (National Journal of Community Medicine, 2020)
Context: The Bhore Committee in 1946 gave the concept of PHC as comprehensive primary health care to the community and maintain an acceptable standard of quality of care. The study was conducted to assess the implementation of National Health Programmes at PHCs in Uttarakhand. Methodology: An observational cross-sectional study was conducted at two PHCs (Thano and Raiwala) from March 2019 to April 2019. Interviews of health functionaries and beneficiaries of national health programmes were done based on standard Indian Public Health Standards (IPHS) guidelines and check list, for both PHCs. Beneficiaries under each programme were also observed. Result: Various programmes such as Universal Immunization Programme, School Health Programme, and Pulse Polio Programme, National nutrition Programme, National family welfare Programme, NPCDCS and Jansankhya Niyantran Yojna were implemented successfully at both PHCs. Although knowledge among peripheral health workers was found to be little inadequate. Conclusion: The functioning and execution of some of the National Health Programs at PHCs Thano and Raiwala were found to be inclined with IPHS guidelines.